(untitled) (Ustozlar uchun, 2025)
This article examines several difficulties associated with using the mother tongue in English language classrooms. The analysis is based on selected literature that discusses effective teaching methods, cultural differences, and the challenges of literal translation. The reviewed studies show that excessive reliance on the mother tongue reduces students’ exposure to English, creates semantic and cultural interference, and often leads to misunderstandings of idioms and phraseological units. The findings highlight the importance of minimizing L1 use and encouraging greater interaction in the target language for more effective learning outcomes.